International Comparison of Higher Education Representatives’ and Students’ Attitudes Towards Feedback Learning - Berková, Kateřina; Frendlovská, Dagmar; Chalupová, Martina; Kubišová, Andrea; Krpálková Krelová, Katarína; Kolářová, Dana (International Journal of Engineering Pedagogy (iJEP), 2023)
The study was conceptualized as a pilot to establish a methodology for comprehensive research with respect to the impact of the proposed learning design on learning outcomes. The aim of the paper is to find out how representatives of higher education institutions and master's students in engineering studies in the Czech Republic and in the countries of Belgium, Germany, Greece, Netherlands, Poland perceive the absence of feedback learning aspects by monitoring the progress of learning. There are many findings on the learning process documented in the literature, but less available are studies of a perceptual nature that identify differences in the attitudes of students and university representatives. The differences between Czech students and International Business Week (IBW) students studying in the Czech Republic and the differences between students and higher education institutions in and outside the Czech Republic are analysed using the Mann-Whitney U test. The strongest absence of the aspects examined by the researchers was found among students from the IBW program studying at Czech higher education institutions. Czech students are the least lacking in these aspects. From the perspective of higher education institutions, partner schools from other countries perceive the absence of the examined aspects in teaching less than higher education institutions from the Czech Republic. The study has theoretical implications for the scientific field, as it has laid the conceptual basis for further research. The study has practical implications for the way higher education teaching is conducted.